TRANSFER DANA BEDA BANK TANPA BIAYA ADMINISTRASI MELALUI APLIKASI FLIP DALAM TINJAUAN ETIKA BISNIS ISLAM - Dwimurti, Bangun Seto (Fakultas Syariah, Universitas Islam Negeri Raden Mas Said Surakarta, 2020)
ABSTRACT Technological development is able to break the old way (disruption) by combining technology and modern finance. The emergence of financial technology or can be called financial technology. Financial Technology is the use of technology in a financial system that produces new products, services, technology and / or business models and can have an impact on monetary stability, financial system stability, and / or the efficiency, smoothness, security and reliability of payment systems. One of the start-ups of financial technology that emerged in the field of fund transfer is Flip. Flip gave rise to new innovations in the field of fund transfers in the form of applications as intermediaries to free the burden of administrative costs that apply to banks. The purpose of this study was to determine the implementation of financial technology transfer of different bank funds without administrative costs through the Flip application and to find out an overview of Islamic business ethics of the transfer of different bank funds without administrative costs through the Flip application. From this study the researchers found the results that the implementation of different bank fund transfers without administrative costs through the Flip application have not fully met the criteria in PBI No. 19 / 12 / PBI / 2017 regarding the Implementation of Financial Technology and Flip has not provided consumer protection if an error occurs due to Flip continues the transfer of funds to the destination account, and there is still business behavior that is not recommended by Islam. Among them are the two processes and a longer time in implementing the transfer of different bank funds without administrative costs and the still unclear (gharār) with the unique code given by Flip and the tyranny in business ventures between startups based on fund transfers. Keywords: Flip Applications; Implementation of Financial Technology; Islamic Business Ethics. ABSTRAK Perkembangan teknologi mampu mendobrak cara lama (disruption) dengan memadukan teknologi dan keuangan modern. Munculah teknologi keuangan atau bisa disebut teknologi finansial. Teknologi Finansial adalah penggunaan teknologi dalam sistem keuangan yang menghasilkan produk, layanan, teknologi, dan/atau model bisnis baru serta dapat berdampak pada stabilitas moneter, stabilitas sistem keuangan, dan/atau efisiensi, kelancaran, keamanan, dan keandalan sistem pembayaran. Salah satu start-up teknologi finansial yang muncul pada bidang transfer dana yaitu Flip. Flip memunculkan inovasi baru dalam bidang transfer dana berupa aplikasi sebagai perantara untuk membebaskan beban biaya administrasi yang berlaku pada bank. Tujuan dilakukan penelitian ini adalah untuk mengetahui penyelenggaraan teknologi finansial transfer dana beda bank tanpa biaya administrasi melalui aplikasi Flip dan untuk mengetahui tinjauan etika bisnis Islam terhadap transfer dana beda bank tanpa biaya administrasi melalui aplikasi Flip. Dari penelitian ini peneliti menemukan hasil bahwa pelaksanaan transfer dana beda bank tanpa biaya administrasi melalui aplikasi Flip belum sepenuhnya sesuai dengan kriteria dalam PBI No.19/12/PBI/2017 tentang Penyelenggaraan Teknologi Finansial dan Flip belum memberikan perlindungan konsumen apabila terjadi kesalahan yang diakibatkan oleh Flip dalam meneruskan transfer dana ke rekening tujuan, serta masih terdapat perilaku bisnis yang tidak dianjurkan oleh Islam. Di antaranya adanya dua kali proses serta waktu yang lebih lama dalam pelaksanaan transfer dana beda bank tanpa biaya administrasi dan masih adanya ketidak jelasan (gharār) dengan adanya kode unik yang diberikan Flip serta adanya kezaliman dalam usaha bisnis antar startup berbasis transfer dana. Kata Kunci: Aplikasi Flip; Etika Bisnis Islam; Penyelenggaraan Teknologi Finansial.